The Implementation and Evaluation of the United States Affordable Care Act - Schultz, David (Medicine, Law & Society, 2019)
In 2010 the United States Congress adopted the Patient Protection and Affordable Care Act (“ACA”), more commonly referred to as Obamacare. The ACA was proposed by President Barack Obama while running for president and it was passed with a near straight party-line vote of Democrats in the US House and Senate in 2010. The ACA was meant to address several problems with the American health care delivery system, including cost, access and outcomes. This article describes the major features of the ACA including the context of the US health care system, evaluates the ACA’s implementation history and assesses its fate and future reforms throughout the presidency of Donald Trump. The overall conclusion based on its implementation is that while the ACA made significant reforms in terms of access to health care, it is not clear that it addressed affordability or began to improve health care outcomes in the US.